ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY AND PRICES ON CUSTOMER SATISFACTION AT VENTION STORE SURABAYA - Fauzan, Dimas (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This research aims to analyze the influence of service quality and price on consumer satisfaction. Service quality and price are important factors in influencing consumer satisfaction in a marketing context. This research was conducted using quantitative research methods and data was obtained through surveys of consumers who had purchased goods and used services from the Vention Store Surabaya that was the object of research. The research results indicate that service quality and price have a significant influence on consumer satisfaction. In conclusion, this research shows that service quality and price play an important role in shaping consumer satisfaction. Companies need to ensure that the services provided to consumers have good responsiveness, provide reliability, guarantees, empathy, and have adequate physical evidence. Apart from that, companies also need to consider competitive pricing strategies and provide value that meets consumer expectations. Thus, companies can increase consumer satisfaction and gain a competitive advantage in the market.